Efficient increase of ɣ-aminobutyric acid (GABA) content in tomato fruits by targeted mutagenesis - Satoko Nonaka; Chikako Arai; Mariko Takayama; Chiaki Matsukura; Hiroshi Ezura (Scientific Reports, 2017)
Abstract γ-Aminobutyric acid (GABA) is a non-proteinogenic amino acid that has hypotensive effects. Tomato (Solanum lycopersicum L.) is among the most widely cultivated and consumed vegetables in the world and contains higher levels of GABA than other major crops. Increasing these levels can further enhance the blood pressure-lowering function of tomato fruit. Glutamate decarboxylase (GAD) is a key enzyme in GABA biosynthesis; it has a C-terminal autoinhibitory domain that regulates enzymatic function, and deleting this domain increases GAD activity. The tomato genome has five GAD genes (SlGAD1–5), of which two (SlGAD2 and SlGAD3) are expressed during tomato fruit development. To increase GABA content in tomato, we deleted the autoinhibitory domain of SlGAD2 and SlGAD3 using clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas)9 technology. Introducing a stop codon immediately before the autoinhibitory domain increased GABA accumulation by 7 to 15 fold while having variable effects on plant and fruit size and yield. This is the first study describing the application of the CRISPR/Cas9 system to increase GABA content in tomato fruits. Our findings provide a basis for the improvement of other types of crop by CRISPR/Cas9-based genetic modification.